Adiabatic process of higher electronically excited states: luminescence from an excited state biradical generated by irradiation of benzophenone‐substituted cyclopropanes†. (9th September 2016) - Matsui, Yasunori; Oishi, Toru; Ohta, Eisuke; Ikeda, Hiroshi; Abe, Manabu; Sheridan, Robert S.
Abstract : Adiabatic photochemical reactions of cyclopropanes possessing a benzophenone moiety ( trans‐ and cis‐ 5 ), which generate a luminescent excited biradical 1 6 *, were studied. Various photochemical and spectroscopic techniques were used for this purpose. Excitation (350 nm, n, π * band) of5 at 77 K affords the lowest excited state 1 5 * that undergoes intersystem crossing to form 3 5 *, which deactivates through phosphorescence. In contrast, 295‐nm excitation ( π, π * band) of5 affords the higher electronically excited state 1 5 **, which undergoes adiabatic C–C bond cleavage reaction to form the excited biradical 1 6 * that luminesces at 630 nm. The results suggest that5 follows 2 photoreaction modes depending on the excitation wavelength, a finding that disobeys Kasha's rule. Abstract : Mechanistic studies on adiabatic photochemical reaction of benzophenone‐substituted cyclopropanes were performed using photochemical (product analysis) and photophysical (spectroscopic) techniques. Analysis of dependence on the excitation wavelengths revealed that adiabatic photochemical reaction takes place not in the lowest excited state but in the higher excited state, contrary to the Kasha's rule.